Approche sémiologique de la publicité télévisée Cas d’Echourouk TV et Ennahar TV - ABBED Chaima (My University, 2022)
Abstract Our modest research work entitled “semiological, approach to television advertising case of EchouroukTV ET EnnaharTV””, falls within the field of semiology, and advertising. The objective of this work is to know how the Algerian culture represented in advertising. In other words, how advertising reflects the dimensions of Algerian culture. Our problem for this research work focuses on the socio-cultural dimensions of Algerians in advertising, that is to say, how the latter acts on its target, taking into consideration the socio-cultural dimensions of Algerian society. As a result, we analyzed Algerian television advertisements, through a semiological analysis, based on Martine Jolly’s analysis grid. After analyzing our corpus, the results obtained from this study shows that: Algerian advertisements carry several dimensions which express the culture of the Algerian community, such as: cultural values, customs and traditions, and architectural heritage. This is in order to consolidate the Algerian culture in the mind of the viewer. -------------------- Résumé Notre modeste travail de recherche intitulé « approche sémiologique de la publicité télévisée, cas d’Echourouk tv et Ennahar tv », S’inscrit dans le domaine de la sémiologie et de la publicité. L’objectif de ce travail est de montrer comment la culture algérienne représentée dans la publicité, autrement dit, comment la publicité reflète les dimensions de la culture algérienne. Notre problématique pour ce travail de recherche porte sur les dimensions socioculturelles des algériens dans la publicité, c’est à dire, comment cette dernière agit sur sa cible, prise en considération les dimensions socioculturelles de la société algérienne. De ce fait, nous avons analysé des publicités télévisées algériennes, à travers une analyse sémiologique, basée sur la grille d’analyse de Martine Joly. Après avoir analysé notre corpus, les résultats obtenus de cette étude montrent que : les publicités algériennes portent plusieurs dimensions qui présentent la culture de la communauté algérien, telles que : les valeurs culturelles, les coutumes et les traditions, et le patrimoine culturel diversifié qui comprend le patrimoine culinaire, vestimentaire et l’architectural. Et ceci afin de consolider la culture algérienne dans l’esprit du spectateur.